Why Leaders Fail Ethically : A Paradigmatic Evaluation of Leadership - Batmanghlich, Cameron A. (Springer International Publishing : Imprint: Springer, 2015)
Contrary to popular conceptions that ethical failures in leadership are correlated with economic downturns and other stressful market conditions, this book argues that such transgressions are an intrinsic element of leadership, as it is defined under the current prevailing paradigm. In recent years the crisis of failures in ethical leadership across organizations, particularly corporations, has been highlighted more than ever, both in academic discourse and the public sphere. Psychological maladies leading to higher number of sick leaves, general feelings of disillusionment among employees, loss of motivation and employee loyalty, even suicide (both in Western corporations and in other parts of the world) are just a few examples of how ethical failures in leadership are expressed. In order to gain original insight into the phenomenon of ethical leadership, the author explores the origins and effects of the current leadership paradigm along two dimensions: (1) a revisit of the leadership construct from a historical and philosophical perspective, with a focus on the relationship between theory and practice; and (2) the theoretical roots of the ethical component of leadership theories, identifying the reasoning behind the value system in our paradigm. Subsequently, by linking these constructs together, a meta-theory emerges suggesting that the three main ethical departure points of virtue ethics, teleology and deontology (all of which have emerged during the past three thousand years through a confluence of the Abrahamic religions' and Greek value systems) are the basis for our reasoning about leadership, its construct and the practice of leadership itself. Challenging traditional views of ethical leadership, the author goes beyond theory and philosophy to consider practical implications, including alternative ways to improve executive recruitment, training and involvement of followers in decision making; experiments like rotating leadership; and an examination of other paradigms, such as Zoroastrianism, hence making an original contribution to the field of leadership both for scholars and practitioners.